Analysis of Errors Committed by Libyan Learners of English Language: A Case Study of Libyan Students at Misurata University (المجلة العلمية لكلية التربية, 2023)
The current study focused on investigating the most frequent morphological, syntactical and spelling errors committed by 41 Libyan learners of the English language department in the Faculty of Education at Misurata University. The study also aimed to identify the leading causes of these errors. For data collection, the researcher selected final examinations writing papers that learners had in the fall semester 2018.  The selected samples were 20 papers of writing I exam and 21 papers of writing II exam. The participants` writings were analyzed using Ellis 1974 (Methodology for Error Analysis). The findings indicated that learners committed 602 morphological, syntactical, spelling errors, which belonged to omission, addition, and misinformation. It is also found that the most frequent type of errors that learners repeatedly committed was omission. The study concluded that omission errors may occur because learners frequently transfer their linguistic knowledge of Arabic to construct English sentences. Most spelling mistakes refer to learners` poor knowledge of English spelling rules.
Keywords: analysis- morphology- errors